2020
DOI: 10.3390/genes11060649
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophosmin 1 Mutations in Acute Myeloid Leukemia

Abstract: Nucleophosmin (NPM1) is a ubiquitously expressed nucleolar protein involved in ribosome biogenesis, the maintenance of genomic integrity and the regulation of the ARF-p53 tumor-suppressor pathway among multiple other functions. Mutations in the corresponding gene cause a cytoplasmic dislocation of the NPM1 protein. These mutations are unique to acute myeloid leukemia (AML), a disease characterized by clonal expansion, impaired differentiation and the proliferation of myeloid cells in the bone marrow. Despite o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 117 publications
(170 reference statements)
2
33
0
Order By: Relevance
“…Studies have shown that the content of NPM1 in tumor cells and growing cells is significantly higher than that in quiescent cells (36,37). Overexpression of NPM1 can promote the growth and proliferation of various tumor cells (5)(6)(7)(8). These results suggest that NPM1 may be a potential target for tumor gene therapy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies have shown that the content of NPM1 in tumor cells and growing cells is significantly higher than that in quiescent cells (36,37). Overexpression of NPM1 can promote the growth and proliferation of various tumor cells (5)(6)(7)(8). These results suggest that NPM1 may be a potential target for tumor gene therapy.…”
Section: Discussionmentioning
confidence: 95%
“…Nucleophosmin 1 (NPM1) is a multifunctional protein that is mainly localized in nucleoli and shuttles between the nucleus and cytoplasm (3). In recent years, the focus of NPM1 research has gradually shifted from hematological diseases to solid tumors (4,5). Previous studies have demonstrated that NPM1 is overexpressed in several types of tumors and promotes the occurrence and progression of tumors (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…While in NK-AML patients, the mutation rate of it is higher, reaching 47% to 60%. [ 42 ] Schnittger et al [ 43 , 44 ] found that positive cases of NPM1 mutations are highly sensitive to chemotherapy-induced remission, complete remission (CR), LFS, and event-free survival. Therefore, the NPM1 gene mutation is considered to be an independent factor that predicts a good prognosis of AML.…”
Section: Discussionmentioning
confidence: 99%
“…This was paralleled by the cooperative impact of these two aberrations on gene expression profiles [23,25]. Interestingly, both FLT3-ITD and NPM1 were also previously shown to shape the epigenome in AML [22,26]. As the process of splicing occurs co-transcriptionally and its regulation was shown to be influenced by chromatin status (including modifications to both histones and DNA), by shaping the epigenome FLT3-ITD and NPM1 mutations have the potential to affect splicing [27][28][29].…”
Section: Introductionmentioning
confidence: 90%
“…FLT3-ITD rarely occurs alone and most frequently coincides with mutations in nucleophosmin (NPM1) with many FLT3-ITD+/NPM1+ AML patients eventually relapsing [1]. NPM1 is a multifunctional protein with diverse physiological roles that include regulation of the cell cycle, DNA damage repair, maintenance of genomic stability and stress response [22]. The molecular synergy between FLT3-ITD and NPM1 mutations was demonstrated to drive rapidly developing AML in mouse models [23,24].…”
Section: Introductionmentioning
confidence: 99%